The benefits and costs of renminbi internationalization - Liqing Zhang; Kunyu Tao (Asian Development Bank Institute (ADBI), 2014)
Despite the increasing recognition that the renminbi (RMB) may eventually become a key global currency, several important questions remain to be answered. This paper analyzes the benefits and costs of the RMB becoming an international currency. The benefits include reduced exchange risk, promotion of the development of the financial market, and expansion of firms in the People's Republic of China. The costs include general costs, which complicate monetary policy and exchange rate policy, and several transitional risks. We argue that the benefits of RMB internationalization should surpass its costs, particularly in the long run, and provide comprehensive policy choices for a sustainable process of RMB internationalization.
Keywords: F42; F31; F36; 330; renminbi internationalization; financial development; transitional risks; international monetary system